Contextual Factors of Performance Measurement Systems Design in Libyan Commercial Banks - Mohamed Elnihewi, Ismail; Mohamed, Rapiah; Hanim, Faudziah (Journal of Advanced Research in Business and Management Studies, 2020)
Based on the contingency theory, this study examines the contextual factors that influence the design of performance measurement systems (PMS). Specifically, this study examines the influence of business strategy and organizational structure on the choice of measurements in Libyan commercial banks. Since the early 1980s, contingency-based research has focused on the search for the best design of management control systems. This research renews this idea by including two factors - business strategy and organizational structure. This research is conducted to contribute to the inconclusive and limited evidence concerning the influence of contextual variables in the design of PMS, particularly in the service industry in less developed countries, such as Libya. The data were gathered from Libyan commercial banks using a survey questionnaire mailed to the branch managers. Data analysis was conducted by employing descriptive analysis, factor analysis, reliability analysis, and multiple regression. The findings show that business strategy has a positive and significant relationship with PMS, while organizational structure has an insignificant influence on PMS design. The results of this study imply that managers should consider the contextual factors that may influence the choice of performance measures, so that the design of their PMS will result in better organizational performance.